STEPPING OUT OF OTHERNESS women of colour finding their inner goddess. - Symons, Rita (ROUTLEDGE, 2025)
What might the impact be on a grown woman of having a nursery school teacher change and anglicise her name at the age of three? That three-year-old was me. In our world, we face more and more polarisation and so it feels imperative that we understand the concept and lived experience of Othering. Othering takes away individuality and reduces whole groups to they. This book explores the theory, examining why Othering is so much part of human biology and conditioning. Through a narrative approach, the experiences of women of colour growing up in 1970s and 1980s Britain are explored, sharing individual stories and common themes. Ultimately this book is a celebration of their deep commitment to self-work and development and their success in navigating the additional burden of being different. We hear from other thinkers and activists, and offer active hope and potential ways forward in how we might create more inclusive, sustainable societies. This is a monumental task but arguably we have no choice, and so the work of changing how we choose to live feels like the most important work we can do together.